2020
DOI: 10.21154/justicia.v17i1.1720
|View full text |Cite
|
Sign up to set email alerts
|

In-Kind Model in Creative Productive Zakat Funds: Case Study on National Zakat Administrator Agency (Baznas) of West Kalimantan Province

Abstract: The results of the research in this paper aim to describe the implementation of the Small Business Capital Program, the constraints in implementing it and the creative productive zakat model that has been implemented by the Baznas of West Kalimantan Province in empowering the economy of Mustahiq. Therefore, the type of research used in this paper is field research with an empirical approach. Data collected from the results of interviews and documentation are then analyzed with qualitative data analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Those results are in line with some studies by Mire (2021) and Indra et al (2020). They found that productive zakat distribution programmes are effective in empowering the poor and reducing economic disparities among the society in Makassar City and West Kalimantan Province.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Those results are in line with some studies by Mire (2021) and Indra et al (2020). They found that productive zakat distribution programmes are effective in empowering the poor and reducing economic disparities among the society in Makassar City and West Kalimantan Province.…”
Section: Literature Reviewsupporting
confidence: 91%
“…These limitations included a shortage of skilled personnel and inadequate funds to monitor the cattle fattening program. Similar findings were reported by Indra et al (2020) who encountered comparable challenges. Ardani and Pujiyono (2021) also found that Zakat institutions in Indonesia had insufficient resources in terms of both quantity and quality.…”
Section: Challengessupporting
confidence: 88%
“…This model uses CWLS profits as a form of zakat funds to purchase production equipment needed by beneficiaries of waqf or mauquf 'alaih. Indra et al (2020) states that the Baznas of West Kalimantan Province has effectively used this model to distribute zakat to mustahik Purchase of production facilities can be in the form of machines or business premises for SMEs and SMEs affected by Covid-19, or initial capital for Muslim community workers who have been laid off.…”
Section: In-kind Modelmentioning
confidence: 99%